Evaluasi Pengembangan Olahraga Daerah: Penilaian Manajemen Pembinaan KONI Lombok Tengah Menuju PORPROV XII 2026 Berbasis CIPP - Hildan; Irmansyah, Johan; Kesuma, Dadang Warta Chanra Wijaya; Muhaimin, Ali (SPORTIVE: Journal Of Physical Education, Sport and Recreation, 2025)
This study evaluated the sports coaching management system at KONI Lombok Tengah in preparation for the 2026 Provincial Sports Week (PORPROV XII) using the CIPP evaluation model (Context, Input, Process, Product). The research adopted a descriptive quantitative approach and collected data from KONI administrators, coaches, and athletes through Likert-scale questionnaires. Results showed that the Context component, particularly the program’s goals, was adequately defined, though background planning lacked depth and data orientation. In the Input domain, infrastructure and funding were sufficient, but the capacity and quality of human resources, especially coaches, remained suboptimal. The Process evaluation revealed strong implementation and coordination, but weak monitoring and feedback systems. The Product analysis showed adequate short-term outcomes but highlighted critical challenges in program sustainability, especially the absence of long-term development strategies and regeneration mechanisms. These findings affirm the utility of the CIPP model in diagnosing strengths and gaps in regional sports development programs and emphasize the urgent need for capacity building, structured evaluation, and long-term planning to ensure sustainable athlete development in resource-constrained settings.